IMPLEMENTASI KEBIJAKAN MENTERI PENDIDIKAN DAN KEBUDAYAAN NO 53 TAHUN 1996 TENTANG SEKOLAH LANJUTAN PERTAMA TERBUKA (STUDI KASUS SMP TERBUKA PEKANBARU) - Ima Silfia Purba; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
How the government of Indonesia handled the prevail of education, are tobuild SMP Terbuka in Pekanbaru city. Because one of the problemthat faced Pekanbaru city iseducationand doesn’t maximal in implementation of SMP Terbuka. The main problem tocompleted the implementation of SMP Terbuka is how to ensured childrenwho graduated from elementary school continue into Junior High School throughSMP Terbuka for the less fortunate. All of the children will geteducationifthe infrastructure is available. This condition can’t be separated fromthe government of Pekanbaru cityto facilitate the infrastructure of education. The research aims to determine implementation of Ministerial Policy of Education and Culture Number 53 Year 1996 About Junior High School Terbuka(Case Study SMP Terbuka Pekanbaru)and examine the factors that influenceimplementation of of Ministerial Policy of Education and Culture Number 53 Year 1996 About Junior High School Terbuka (Case Study SMP Terbuka Pekanbaru).Theoretical concept used ispublic policy, education policyand implementationin Van Meter and Van Hornwho said thatthere are 6 variablesin implementationsuch as: 1. Standards and policy goals, 2. resource, 3. Communication between organizations, 4. Characteristics of implementers, 5. political, economic and social condition, 6. Dispositon.Result of the research showedthat implementation of Ministerial Policy of Education and Culture Number 53 Year 1996 About Junior High School Terbuka (Case Study SMP Terbuka Pekanbaru)is not optimally yet. Known from bad communication, between the government, school and society. This is caused by limited human resources,infrastructurelikethe budget is insufficientfrom Dinas Pendidikan Provinsi Riau to achieve SMP Terbuka and education facility is insufficient, social and economic condition of the society is underprivileged. This resultedthat implementation of Ministerial Policy of Education and Culture Number 53 Year 1996 About Junior High School Terbuka is not maximal in Pekanbaru.Keyword :Implementation, Education and SMP Terbuka